Neurological complications of SARS-CoV-2 infection among solid organ transplanted patients: does immunosuppression matter? - Avorio, Federica; Russelli, Giovanna; Panarello, Giovanna; Alduino, Rossella; Conaldi, Pier Giulio; Lo Re, Vincenzina (Frontiers in Neurology, 2024)
Introduction SARS-CoV-2 infection can lead to a broad range of neurological manifestations such as olfactory and gustative disorders, myalgias, headache, and fatigue but also more rare and severe neurological pictures such seizures, encephalitis, and cerebrovascular diseases. It is still unknown if the underlying pathophysiological mechanism is the direct cytotoxic effect of the virus on central nervous system or if the related systemic inflammation leads to cerebral suffering and neurological symptoms. Studying neurological manifestations of SARS-CoV-2 infection among solid organ transplant recipients, who take immunosuppressive drugs, may help to shed light on this topic. Methods We enrolled a total of 73 solid organ transplantation recipients (kidney, liver, lung, heart and combined) with a history of SARS-CoV-2 infection (in the period between July 2020 and June 2021). We collected all demographic and clinical general information and, through phone interviews, we registered retrospectively the occurrence of neurological symptoms during the acute phase of infection and within the next 6 months. Results Approximately 27.4% (20/73) of patients needed hospitalization during the infection, 25.3% (18/73) were treated with oxygen therapy, and only one patient was admitted to the Intensive Care Unit for mechanical ventilation. Almost 74% (54/73) of patients reported at least one neurological symptom/disease. The most frequent neurological complications were myalgia (57.5%), headache (37%), and hyposmia/hypogeusia (37%). Need of oxygen therapy during the SARS-CoV-2 infection was statistically significantly associated to neurological complications (p= 0.0344). Pre-infection neurological comorbidities and immunosuppression levels (higher levels of tacrolimus and also being on steroids) did not modify the probability to have neurological manifestations. Discussion Frequency of headache was comparable with the same self-reported symptom in the general population, while hyposmia/hypogeusia was more frequent in our cohort of transplant recipients. Higher level of tacrolimus as well as being on steroids did not result protective against neurological manifestation. Lastly neurological symptoms occurred more frequent in more severe cases of infection.